CARD8 gene variant is a risk factor for recurrent surgery in patients with Crohn's disease. Issue 11 (November 2015) - Germain, Adeline; Guéant, Rosa-Maria; Chamaillard, Mathias; Bresler, Laurent; Guéant, Jean-Louis; Peyrin-Biroulet, Laurent
Abstract Background and aims Post-operative recurrence is frequent in Crohn's disease. Genetic factors associated with post-operative recurrence remain poorly understood. Identification of genetic variants associated with repeat surgery would allow risk stratification of patients who may benefit from early aggressive therapy and/or post-operative prophylactic treatment. Methods Crohn's disease patients who had at least one bowel resection were retrospectively identified from the "Nancy IBD cohort". Covariates and potential interactions were assessed using the Cox proportional hazard model. Kaplan–Meier curves for time to surgical recurrence were developed for 200 genetic variants and analyzed with the log-rank test. Results 137 patients had at least 1 resection in our cohort: 38 had a surgical recurrence (28%). In multivariate analysis, current smoker status (OR 6.97, 95% CI 1.85–26.22, p = 0.004), post-operative complications after prior surgery (OR 2.72, 95% CI 1.02–7.22, p = 0.044), and Caspase recruitment domain-containing protein 8 (CARD8) homozygosity for the risk allele (OR 7.56, 95% CI 1.13–50.37, p = 0.036) remained significantly and independently associated with surgical recurrence. Conclusion Current smoker status was associated with increased risk of surgical recurrence. A novel association between CARD8 and increased risk of surgical recurrence in Crohn's disease was observed. CARD8 could be a new marker for risk stratification and prevention of recurrent surgery.